Does Severe Hypokalemia Worsen the Outcome of Diabetic Ketoacidosis - Pamela Sandhya De Jaka; Dias Guita Alantus (PP PERKENI, 2024)
Hypokalemia is an uncommon finding in the initial evaluation of patients with DKA before insulin treatment. However, it can complicate the management of DKA and lead to a worse prognosis. Hypokalemia in DKA may result from a combination of factors, including kaliuresis, secondary osmotic diuresis, inadequate oral intake, and gastrointestinal losses such as vomiting. We report the case of a 31-year-old woman who recently experienced diabetic ketoacidosis with severe dehydration, severe hypokalemia, and sepsis. Unfortunately, her condition deteriorated, and she eventually went into cardiac arrest while receiving treatment in the emergency unit. This case highlights the challenges involved in providing therapy and managing complications that arise in patients, presenting a dilemma for healthcare providers